Construct validity and reliability of manufacturing industry: a rasch measurement model approaches for pilot study - Zaliza Hanapi (Tanjong Malim, 2019)
Construct validity and reliability of manufacturing industry: a rasch measurement model approaches for pilot study by Zaliza Hanapi